How an Agricultural Development Bank Revolutionized Rural Finance: The Case of Bank Rakyat Indonesia - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2000)
The case of BRI is evidence that, in a deregulated policy environment, a government-owned agricultural development bank can (a) be transformed into a highly profitable, self-reliant financial intermediary, and (b) turn into a major microfinance provider, offering carefully crafted microsavings and microcredit products to low-income people at market rates of interest. Making good use of government seed money and a World Bank loan during an initial phase, it has now fully substituted savings deposits for external loans as its source of funds. With an outreach to 25.1 million saving accounts and 2.6 million borrowers (July 2000) through a network of 3,700 village units operating as profit centers, BRI covers its costs from the interest rate margin and finances its expansion from its profits. With non-targeted loans from 5 to 5000 at rural market rates of interest and unrestricted deposit services, the BRI Microbanking Division has weathered the Asian financial crisis well, making BRI the only profitable government bank in Indonesia. Several lessons can be drawn from BRI's experience: – Financial sector policies work and are conducive to financial innovations – With attractive savings and credit products, appropriate staff incentives, and an effective system of internal regulation and supervision, rural microfinance can be profitable – The poor can save; rural financial institutions can mobilize their savings cost-effectively – If financial services are offered without a credit bias, demand for savings deposit services exceeds the demand for credit by a wide margin – Incentives for timely repayment work – Outreach of a financial institution to vast numbers of low-income people and financial selfsufficiency (including viability and self-reliance) are compatible – Average transaction costs can be lowered, and both the profitability of a financial institution and the volume of loanable funds can be increased by catering for both the poor and the non-poor with their demands for widely differing deposit and loan sizes Within a six-year period,1984-90, BRI became a model case in Asia of the transformation of an ailing government-owned agricultural development bank into a viable and self-sufficient financial intermediary with ever-increasing financial resources and numbers of customers, competing successfully with an array of other local financial institutions. Further strength was added to BRI?s microfinance operations during the Asian financial crisis: When the Indonesian banking system collapsed, BRI?s Microbanking Division remained profitable, with profits amounting to 150 million in 1999. At the peak of the crisis, 6-8/1998, it attracted 1.29 million new savers during that three-month period alone, while demand for credit, because of perceived uncertainties, stagnated. This has generated excess liquidity of US1.45 billion (July 2000) – a recurrent challenge during the 100-year history of BRI and its predecessors. Since the onset of the Asian financial crisis, the division?s 12-month loss ratio has been continually dropping to 1.35% (July 2000), substantially below its already low long-term loss ratio of 2.1% (1984-1999). Inspired by the success of BRI and some other institutions in the region, governments and donors may focus their resources on the transformation of agricultural development banks into viable, selfsustained microfinance intermediaries, instead of closing them down.
Keywords: 330